Gairo virus, a novel arenavirus of the widespread Mastomys natalensis: Genetically divergent, but ecologically similar to Lassa and Morogoro viruses - Gryseels, Sophie; Rieger, Toni; Oestereich, Lisa; Cuypers, Bart; Borremans, Benny; Makundi, Rhodes; Leirs, Herwig; Günther, Stephan; Goüy de Bellocq, Joëlle (Virology, 2015)
Despite its near pan-African range, the Natal multimammate mouse, Mastomys natalensis, carries the human pathogen Lassa virus only in West Africa, while the seemingly non-pathogenic arenaviruses Mopeia, Morogoro, and Luna have been detected in this semi-commensal rodent in Mozambique/Zimbabwe, Tanzania and Zambia, respectively. Here, we describe a novel arenavirus in M. natalensis from Gairo district of central Tanzania, for which we propose the name "Gairo virus". Surprisingly, the virus is not closely related with Morogoro virus that infects M. natalensis only 90km south of Gairo, but clusters phylogenetically with Mobala-like viruses that infect non-M. natalensis host species in Central African Republic and Ethiopia. Despite the evolutionary distance, Gairo virus shares basic ecological features with the other M. natalensis-borne viruses Lassa and Morogoro. Our data show that M. natalensis, carrying distantly related viruses even in the same geographical area, is a potent reservoir host for a variety of arenaviruses.
Keywords: virus Lassa; Virology; Disease Reservoirs; Arenavirus; Phylogeny; Molecular Sequence Data; molekulární sekvence - údaje; zdroje nemoci; Female; Mastomys natalensis; Murinae; zvířata; Arenaviridae Infections; Hemorrhagic fevers; Tanzanie; genetická variace; Genetic Variation; Zoonotic infections; ženské pohlaví; Male; fylogeneze; Tanzania; nemoci hlodavců; protilátky virové; Antibodies, Viral; Animals; mužské pohlaví; Lassa virus; infekce viry z čeledi Arenaviridae; Rodent Diseases; Ecology